THE FACTORS EFFECTING THE SUPPLY CHAIN SUCCESS: AN EMPIRICAL EVIDENCE FROM AUTOMOBILE INDUSTRY IN CHINA - Yajid, Mohd Shukri Ab ,; Shukri, Shakeerah Mohd; Tham, Jacquline (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to develop an experiential model to test the factors which can influence the supply chain partnerships in the automobile industry in China. The research is based on both primary data and secondary data. The primary data was collected from both automobile manufacturers and suppliers using a specially developed questionnaire – the total numbers of respondents were 128 managers from the companies sampled. The survey was analyzed using two statistical tools, which are Regression and T – tests. The results of survey proved that the level of supply chain technologies usage is still very low and it indicated that there are eight factors influence the supply chain partnerships in auto industry in China, which include “trust”, “commitment”, “culture”, “human involvement”, “training and education”, as well as “stability of demand”, “problem specific capability” and “adequate measurement of IT infrastructure”. The further improvement of IT infrastructure of supply chain and interaction partnerships should be considered in order to keep the long – term relationship among partners.